Mass spectrometry-guided isolation of two new dihydrobenzophenanthridine alkaloids from Macleaya cordata. Issue 14 (18th July 2017) - Qing, Zhi-Xing; Yang, Peng; Yu, Kun; Yang, Xue-Yi; Liu, Jing-Hong; Xiang, Feng; Cao, Hua-Liang; Cheng, Pi; Zeng, Jian-Guo
Abstract: Two new alkaloids 6-hydroxyethyldihydrochelerythrine (1 ) and 6-hydroxymethyl-7, 8-demethylenedihydrochelerythrine (2 ) together with two analogues named maclekarpine E (3 ) and 6-hydroxymethyldihydrosanguinarine (4 ) were detected primarily from the leaves of Macleaya cordata by their characteristic mass spectrometry (MS) and tandem mass spectrometry (MS/MS). And then isolation of four targeted-compounds was performed by column chromatography and preparation HPLC under the guiding of MS. Finally, their structures were determined by spectrum analysis. Alkaloids3 and4 were isolated from this plant medicine for the first time. Abstract :